Completely suppressed high-voltage phase transition of P2/O3-Na0.7Li0.1Ni0.1Fe0.2Mn0.6O2via Li/Ni co-doping for sodium storage. Issue 20 (31st August 2022) - Wang, Yunpeng; Yan, Mengmeng; Xu, Kang; Chang, Yu-Xin; Guo, Jin; Wang, Qinghua; Wang, Bin; Wang, Duan; Yin, Ya-Xia; Xu, Sailong
Abstract : A novel P2/O3-Na0.7 Li0.1 Ni0.1 Fe0.2 Mn0.6 O2 cathode is prepared via Li/Ni co-doping, and delivers attractive cycling and rate performances due to the high Na + diffusion coefficient and the complete suppression of the high-voltage P2–Z phase transition. Abstract : P2-type Fe, Mn-based layered oxides have been potential cathode materials for sodium-ion batteries (SIBs), yet suffer from their intrinsic sluggish kinetics and structural instability due to the adverse P2–Z high-voltage phase transition. An improvement strategy by either single-cation doping or co-doping is used, but typically with either a lowered reversible capacity or partially suppressed high-voltage phase transition. In this study, a novel biphasic P2/O3-Na0.7 Li0.1 Ni0.1 Fe0.2 Mn0.6 O2 cathode was prepared, with the high-voltage phase transition completely suppressed via Li/Ni co-doping. Inactive Li + stabilizes the structure and active Ni 2+ improves the electrical conductivity, while the P2/O3 intergrown structure induced by co-doping further limits the lattice stress during cycling. The resulting cathode exhibits an outstanding rate capability (102.2 mA h g −1 at 0.1C and 59.8 mA h g −1 at 10C), and an excellent cyclic stability (74.6% capacity retention after 500 cycles at 10C). The reaction kinetics and structural evolution demonstrate high Na + diffusion coefficient and the complete suppression of the Z phase transition, respectively, both of which underpin the enhancement. The results highlight that the synergistic effect between Li/Ni co-doping and accompanying biphasic structure promises an effective improvement strategy to develop high-performance Fe, Mn-based and Co-free layered cathode materials for SIBs.